2021
DOI: 10.1002/jbt.22744
|View full text |Cite
|
Sign up to set email alerts
|

Increased oxidative stress and mitochondrial impairments associated with increased expression of TNF‐α and caspase‐3 in palmitic acid‐induced lipotoxicity in myoblasts

Abstract: Saturated fatty acids, whose circulating levels are markedly increased in the body, significantly affect the growth and functions of skeletal muscle. These fatty acids may exert a detrimental effect on the undifferentiated skeletal myoblasts that may adversely affect their differentiation. In the present study, the exposure of myoblasts to excess palmitic acid caused an elevation of tumor necrosis factor‐α expression and an increase in reactive oxygen species levels consistent with the enhanced inflammation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…However, while most studies have detected increased oxidative stress after PA treatment in other cell types [189,190] as the most likely cause of DNA damage the study from Ishaq and coworkers [5] did not find an increase in mitochondrial superoxide after PA treatment suggesting alternative mechanisms for the induction of DNA damage. There are some alternative pathways that could explain the occurrence of DNA damage without measurable mitochondrial superoxide levels.…”
Section: Palmitic Acid As An Inducer Of Senescence In Human Adipocyte...mentioning
confidence: 88%
See 1 more Smart Citation
“…However, while most studies have detected increased oxidative stress after PA treatment in other cell types [189,190] as the most likely cause of DNA damage the study from Ishaq and coworkers [5] did not find an increase in mitochondrial superoxide after PA treatment suggesting alternative mechanisms for the induction of DNA damage. There are some alternative pathways that could explain the occurrence of DNA damage without measurable mitochondrial superoxide levels.…”
Section: Palmitic Acid As An Inducer Of Senescence In Human Adipocyte...mentioning
confidence: 88%
“…However, Ishaq and co-authors only found trends for increase of inflammatory markers after PA treatment in subcutaneous adipocytes in vitro [5]. Previous studies had demonstrated that increased contact of adipocytes with PA promoted direct detrimental intracellular effects [189][190][191]. There are two main pathways for PA-induced cellular stress: endoplasmic reticulum (ER) stress and mitochondrial ROS generation.…”
Section: Co-treatment Of Oa and Pa In Donor-derived Isogenic Subcutan...mentioning
confidence: 99%
“…However, while most studies have detected increased oxidative stress after PA treatment in other cell types [189,190] as the most likely cause of DNA damage the study from Ishaq and coworkers [5] did not find an increase in mitochondrial superoxide after PA treatment suggesting alternative mechanisms for the induction of DNA damage. There are some alternative pathways that could explain the occurrence of DNA damage without measurable mitochondrial superoxide levels.…”
Section: Palmitic Acid As An Inducer Of Senescence In Human Adipocyte...mentioning
confidence: 99%
“…However, Ishaq and co-authors only found trends for increase of inflammatory markers after PA treatment in subcutaneous adipocytes in vitro [5]. Previous studies had demonstrated that increased contact of adipocytes with PA promoted direct detrimental intracellular effects [189][190][191]. There are two main pathways for PA-induced cellular stress: endoplasmic reticulum (ER) stress and mitochondrial ROS generation.…”
Section: Co-treatment Of Oa and Pa In Donor-derived Isogenic Subcutan...mentioning
confidence: 99%
“…As a driver of lipotoxicity, it has been shown that excessive PA mediated increase in cellular reactive oxygen species (ROS) activates cell apoptosis in different cell types, including HepG2 cells [3], porcine intestinal epithelial cells [4] and HT-22 cells [5]. Significantly, in higher energy requirements myocytes, excessive PA also caused a decrease in mitochondrial membrane potential (MMP) [6,7], mitochondrial respiratory capacity [8,9], and destroyed mitochondrial DNA and morphology by decreasing the protein expression of mitochondrial fusion, fission, biogenesis, which in turn leads to cell death. Thus, we hypothesized that PA may could also induce a mitochondrial dysfunction in BEECs, which in turn activate the apoptotic pathway.…”
Section: Introductionmentioning
confidence: 99%